Investigation of Ozone Microbubbles for the Degradation of Methylene Orange Contaminated Wastewater - Nashmi, Ola A; A. Mohammed, Ahmed; N. Abdulrazzaq, Nada (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In the present study, semi – batch experiments were conducted to investigate the efficiency of ozone microbubbles (OMBs) in the treatment of aqueous dye solutions methylene orange under different reaction conditions such as  effect of initial solution pH , ozone generation rate and initial MO-concentration. The results showed that the removal of MO by OMBs were very high at the acidic and alkaline media and upon increasing the generation rate of ozone from 0.498 to 0.83 mg/s, the removal efficiency dramatically increased from 75to 100% within 15 min. The rate of oxidation reaction followed a pseudo first- order kinetic model. The results demonstrated that OMBs is efficient in terms of the decline of methylene orange concentration and its total mineralization.